2020
DOI: 10.1111/jcmm.16080
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mosaicism detected by karyotyping and chromosomal microarray analysis in prenatal diagnosis

Abstract: Chromosomal mosaicism (CM) is a biological phenomenon defined as an individual who has arisen from a single zygote and has two or more populations of cells with distinct genotypes. 1 The main underlying mechanisms leading to mosaicism formation involve mitotic or meiotic non-disjunction errors, anaphase lagging and trisomy rescue, endoreplication events, and uniparental disomy (UPD) associated with trisomy rescue. 2 Theoretically, the pattern of the mosaic distribution in the foetus and placenta is largely det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…For the mosaic balanced translocation, although CMA result was normal, we couldn't discriminate it between truly balanced and unbalance. [13] In this study, we used CMA(SNP array platform) and karyotype analysis for prenatal diagnosis of pregnant women with abnormal DS screening results. CMA is equivalent to traditional karyotype analysis for the prenatal diagnosis of aneuploidies.…”
Section: Overall Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the mosaic balanced translocation, although CMA result was normal, we couldn't discriminate it between truly balanced and unbalance. [13] In this study, we used CMA(SNP array platform) and karyotype analysis for prenatal diagnosis of pregnant women with abnormal DS screening results. CMA is equivalent to traditional karyotype analysis for the prenatal diagnosis of aneuploidies.…”
Section: Overall Resultsmentioning
confidence: 99%
“…CNVs are determined by measuring the absolute uorescence probe intensities of the patient sample compared with the intensities of multiple normal controls. [13] In this study, we used CMA(SNP array platform) and karyotype analysis for prenatal diagnosis of pregnant women with abnormal DS screening results. CMA is equivalent to traditional karyotype analysis for the prenatal diagnosis of aneuploidies.…”
Section: Discussionmentioning
confidence: 99%
“…CMA is a molecular genetics technique developed in recent years. 34 CMA has signi cant advantages because it can detect chromosome microdeletions or microduplications that cannot be detected by conventional karyotype analysis at the genome level. [35][36][37] However, CMA cannot detect balanced structural translocation and low proportion chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors that cause FGR have rarely been reported, and some studies that reported a genetic association were conducted with small sample sizes [ 5 ]. Single-nucleotide polymorphism array (SNP-array) can detect copy number variations (CNVs) at a genome-wide level, as well as chimeras (> 30%), loss of heterozygosity, and uniparental disomy (UPD) [ 6 , 7 ]. SNP-array has been widely used in the diagnosis of fetal structural malformations, primary mental retardation, growth and developmental retardation, autism, and tumors [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%